2018
DOI: 10.24843/eja.2018.v24.i01.p25
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pendapatan Asli Daerah terhadap Pertumbuhan Ekonomi dengan Belanja Modal dan Investasi Swasta sebagai Pemoderasi

Abstract: ABSTRAKPertumbuhan Ekonomi merupakan salah satu indikator untuk mengukur keberhasilan pembangunan ekonomi dalam suatu negara. Diharapkan dengan adanya penerimaan dari PAD dapat meningkatkan Pertumbuhan Ekonomi daerah, peningkatan PAD dapat meningkatkan Belanja Modal pemerintah daerah, pemerintah daerah perlu memberikan perhatian khusus dalam bidang investasi swasta. Penelitian ini adalah untuk mengetahui pengaruh pendapatan asli daerah terhadap pertumbuhan ekonomi dengan belanja modal dan investasi swasta seba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 2 publications
3
6
0
11
Order By: Relevance
“…It means that if DAK has increased, then the capital expenditure of districts/cities in Kalimantan will increase significantly. This result aligns with Pratiwi et al (2018) and Saraswati and Ramantha (2018), which showed that DAK has a positive and significant effect on capital expenditure. Therefore, it can be concluded that H2 is supported.…”
Section: The Effect Of Special Allocation Funds (Dana Alokasi Umum-dak) On Capital Expenditures (Belanja Modal-bm)supporting
confidence: 92%
See 2 more Smart Citations
“…It means that if DAK has increased, then the capital expenditure of districts/cities in Kalimantan will increase significantly. This result aligns with Pratiwi et al (2018) and Saraswati and Ramantha (2018), which showed that DAK has a positive and significant effect on capital expenditure. Therefore, it can be concluded that H2 is supported.…”
Section: The Effect Of Special Allocation Funds (Dana Alokasi Umum-dak) On Capital Expenditures (Belanja Modal-bm)supporting
confidence: 92%
“…Additionally, the budget occupies a highly significant position. When an organization's resources are acquired and used, a budget is a detailed plan formally stated in quantitative terms, usually in units of money (financial planning), to show the acquisition and use of those resources (Saraswati & Ramantha, 2018). According to Fatimah et al (2019), the public budget contains activity plans represented in income and expenditure acquisition plans in monetary units described in the form of income and expenditure acquisition plans in monetary units.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This study cannot prove the influence of PAD on regional economic growth. These results are not in accorandance with the results of research from Barimbing & Karmini (2015); Kusumawati & Wiksuana (2018); Maryati (2010); Mawarni et al (2013); Rori et al (2016); Saraswati & Ramantha (2018); Setiyawati & Hamzah (2007). When viewed from its contribution to the APBD, Kuningan's PAD is classified as exceedingly small.…”
Section: The Effect Of Pad On Economic Growthmentioning
confidence: 62%
“…Gemmell et al (2013) research explained that income decentralization was associated with higher income. Some studies, Barimbing & Karmini (2015); Kusumawati & Wiksuana (2018); Maryati (2010); Mawarni et al (2013); Rori et al (2016); Saraswati & Ramantha (2018); Setiyawati & Hamzah (2007) could prove that PAD had a positive effect on regional economic growth. Based on that, the first hypothesis in this study is: H1: Local Regional Revenue positively influences the regional economic growth.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 97%